2003
DOI: 10.2174/1568010033344453
|View full text |Cite
|
Sign up to set email alerts
|

CCR3 and CXCR3 as Drug Targets for Allergy: Principles and Potential

Abstract: Atopic disorders include a range of conditions such as allergic asthma, -rhinitis, -conjunctivitis, -dermatitis, food and drug allergies and anaphylaxis. Induction of T helper (Th)-2 immune response with consequent IgE dependent eosinophil, basophil and mast cell mediated tissue damage is the characteristic feature of allergies. The mechanism underlying this unique and long appreciated feature of allergy is being elucidated at the molecular level with advances in our knowledge of the chemokine system. Thus, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In general, it is well-known that during allergic responses, the levels of Th2 cytokine tend to increase while the Th1 cytokine levels tend to decrease [31,32]. We found that the levels of both IFN-γ and IL-4 were significantly increased.…”
Section: Discussionmentioning
confidence: 51%
“…In general, it is well-known that during allergic responses, the levels of Th2 cytokine tend to increase while the Th1 cytokine levels tend to decrease [31,32]. We found that the levels of both IFN-γ and IL-4 were significantly increased.…”
Section: Discussionmentioning
confidence: 51%
“…Less commonly, the reaction occurs after a particular food or drug has been taken by mouth. Atopic disorders include a range of conditions such as allergic asthma, rhinitis, conjunctivitis, dermatitis, food and drug allergies, and anaphylaxis (Gangur et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis suggests marked elevation of a single cytokine in the heart -IL-6 and elevation of a small group of chemokines (CCL9/11/12 and CXCL1/2). It is noteworthy that all these mediators are known to be important mediators in mast cell biology and allergic reactions (Gurish and Austen 2012;Jia et al 1996;Gangur et al 2003;Zhang et al 2007;Tsujino et al 1993). Furthermore, comparing mice that were sensitized vs. those that were sensitized plus oral challenged we noted that elevation of these mediators in the heart tissue was largely in response to oral allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine CCL9, an agonist of CCR1 contributes to hypersensitivity reactions (Lean et al 2002). Chemokines CCL11/12 are known to signal the chemokine receptor CCR3 -a critical chemokine receptor in allergic responses and in coordinating cellular traffic in the allergic inflammatory tissues (Kitaura et al 1996;Gangur et al 2003). Thus, the elevation in these mediators in the heart tissue provide molecular evidence for allergic inflammation in the heart.…”
Section: Discussionmentioning
confidence: 99%